Multidisciplinary Team Management In Saudi Healthcare: A Systematic Review Of Evidence, Challenges And Opportunities (The Review of Diabetic Studies, 2025)
Background:Multidisciplinary team (MDT) management is central to improving patient outcomes and healthcare efficiency through collaborative practice. In Saudi Arabia, MDT implementation supports Vision 2030 goals of integrated and patient-centered care, yet organizational and cultural barriers continue to limit its full adoption.Aim:This systematic review aimed to evaluate the existing evidence, challenges, and opportunities surrounding multidisciplinary team management within Saudi healthcare, highlighting its impact on patient outcomes, organizational efficiency, and healthcare transformation..Method:Following PRISMA guidelines, five databases PubMed, Scopus, CINAHL, ScienceDirect, and Google Scholar were searched for studies published between 2021 and 2025. After screening 145 records and applying inclusion criteria, 10 primary studies were included. Quality appraisal was conducted using CASP and JBI tools, and data were thematically synthesized under key domains: effectiveness, challenges, and opportunities.Results:Findings revealed that effective MDT implementation improved patient safety, reduced medical errors, and enhanced satisfaction and service efficiency. However, challenges included hierarchical structures, unclear professional roles, limited interprofessional education, and inconsistent digital integration. Strong leadership, standardized communication, and national policy support were identified as enablers for sustainable MDT practice.Conclusion:Multidisciplinary team management significantly advances Saudi healthcare quality and aligns with Vision 2030 reforms. To maximize its potential, emphasis must be placed on structured interprofessional education, technological integration, and leadership-driven cultural change to embed collaboration as a systemic standard of care.